Dimensi Sociopreneurship pada Usaha Agribisnis Wijaya Vegetables di Desa Baturiti Kecamatan Baturiti Kabupaten Tabanan - YANTI, JUNI; SUARDI, I DEWA PUTU OKA; SUTARI, NI WAYAN SRI (Jurnal Agribisnis dan Agrowisata (Journal of Agribusiness and Agritourism); Vol.12, No.1, Juli 2023DO - 10.24843/JAA.2023.v12.i01.p25, 2023)
Dimensions of Sociopreneurship in Wijaya Vegetables Agribusiness Business in Baturiti Village, Baturiti District, Tabanan Regency The uncertain market coupled with the view of dirty farmers among the millennial generation makes work as a farmer even more forgotten. So it is important to increase the interest of the younger generation in the agricultural sector, one of which is by entrepreneurship in the sociopreneurship nuanced agriculture. Wijaya Vegetables is located in Baturiti District, Tabanan Regency, Bali Province. Data collection methods used are interview techniques and direct observation. This business model becomes a 'marketer' so that fair trade occurs between farmers and consumers so that they are able to break the long market chain. Farmers' harvests will be marketed directly to consumers with a profit allocation of 25% for business expansion plans, 30% for social programs and 45% for three HR management. In the social aspect, Wijaya Vegetables has carried out the sociopreneurship dimension starting from social value in the form of providing markets to farmers from upstream to downstream, while for civil society in the form of giving donations to the surrounding community. In innovation, this business makes short, medium and long term innovations. Finally, on economic activity, Wijaya Vegetables creates economic activities that have a positive impact on farmers sales.